(untitled) (Journal of Oriental Studies, 2017)
This article is devoted to the study of system of the characters in the main and famous story «Seoul, The Winter of 1964» by the remarkable writer of Korea in 1960s Kim Seung Ok. In this story Kim Seung Ok keenly reveals phsycho-social problems that were existed in capitalist Korean society during the 1960s, such as crisis of human relationship, alienation from society, hopelessness, uncertainty, confusion and discourtesy by describing and portraying the lives and fates of each character, as well as relationship between them.